Osthole Induces Apoptosis and Caspase-3/GSDME-Dependent Pyroptosis via NQO1-Mediated ROS Generation in HeLa Cells. (8th June 2022) - Wang, Juan; Huangfu, Mengjie; Li, Xiaojuan; Han, Mengjie; Liu, Guoxiang; Yu, Dan; Zhou, Luwei; Dou, Tong; Liu, Yisa; Guan, Xiao; Wei, Riming; Chen, Xu
Abstract : Osthole is a natural coumarin which has been proved to inhibit growth of cancer cells by inducing cell death, while its mechanism was considered to be just caused by apoptosis. In our study, we found that osthole activated not just apoptosis, but also pyroptosis which is a form of regulated cell death accompanied by loss of cell membrane integrity and lactate dehydrogenase (LDH) release. Caspase-3 is a key protein of apoptosis as well as pyroptosis. The apoptosis and pyroptosis induced by osthole were all inhibited by irreversible caspase-3 inhibitor Z-DEVD-FMK. Meanwhile, knockdown of gasdermin E (GSDME) only reduced the osthole-induced pyroptosis but did not affect the occurrence of apoptosis. Our proteomic analysis revealed that the expression of NAD(P)H: quinone oxidoreductase 1 (NQO1) was decreased in osthole-treated cells. Moreover, NQO1 inhibition by osthole induced the overproduction of reactive oxygen species (ROS), as well as apoptosis and pyroptosis. ROS inhibitor N-Acetyl-L-cysteine (NAC) not only reduced osthole-induced apoptosis but also reversed its effect on the pyroptosis. Meanwhile, knockdown of NQO1 by si-NQO1 or its inhibitor dicoumarol (DIC) not only enhanced ROS generation but also strengthened the GSDME-mediated pyroptosis. Finally, we demonstrated that osthole inhibited tumor growth and the expression of NQO1 in a HeLa xenograft mode. Similar to the results in vitro, osthole stimulated the activation of caspase-3, PARP, and GSDME in vivo . Taken together, all these data suggested that osthole induced apoptosis and caspase-3/GSDME-mediated pyroptosis via NQO1-mediated ROS accumulation.